The decision of desire - Lippi, Silvia (Univocal book., 2020)
"The Decision of Desire is a thorough and highly inventive interpretation of the whole of Lacan's work, with an emphasis on the "late Lacan" of the 1970s, with respect to the broad question of what exactly psychoanalysts mean when they speak of desire"--